Drying kinetics of soybean grains - Silva, Lays Português; dos Santos, Samuel Gonçalves Ferreira; Queiroz, Juliano Silva; Rodovalho, Renato Souza; Buso, Wilian Henrique Diniz (Científica, 2020)
Soybean (Glycine max) is one of the most important crops in grain production in Brazil. Its grains are destined for the domestic market and mainly for export. Thus, it is necessary to guarantee the quality of stored grains for later consumption. Drying is a preprocessing step to preserve grains and improve their quality during storage. This study evaluates the drying kinetics of soybean grains to determine effective diffusivity and thermodynamic properties. Soybean samples were collected at the Federal Institute of Goiás - Ceres Campus. Moisture content was approximately 0.21 (decimal db). The samples were subjected to drying at temperatures of 20, 30, 40, and 50 °C until hygroscopic equilibrium was reached. Ten mathematical models were used to fit the drying data, using the following statistical criteria: relative mean error (P), estimated mean error (SE), chi-square (χ²), coefficient of determination (R²), and residual distribution. The effective diffusion coefficient and the activation energy were obtained through the selected mathematical model and the Arrhenius equation. The dryings started with RX close to 0.82 and finished with hygroscopic equilibrium. The average drying time was 9 hours and 30 minutes. The mathematical model of Midilli best fit the drying kinetics of soybean grains. The activation energy obtained was 26.80 kJ mol -1 , standard for agricultural products. As the drying air temperature rises, the effective diffusion coefficient increases from 2.2642 10 -9 to 5.6325 10 -9 m² s -1 , common values for grains. The increase in the drying air temperature increases Gibbs free energy while decreasing enthalpy and entropy, a behavior common to grains for different temperatures.